Memória(s) na Comunidade Remanescente de Quilombo Serra do Apon-PR: algumas formas de narrar a vida - Souza, Suzimara Ferreira de (2018)
This dissertation is part of the Postgraduate Program in Language Studies of the Ponta Grossa State University (UEPG) and aims to understand how the memory of the subjects belonging to CRQSerra do Apon, a region located in the interior of Castro-PR, is represented by the oral and visual narratives produced by the subjects' gaze. To reflect on the relation time and memory, we use authors Maurice Halbwachs (2013) and Pierre Nora (1993). From the idea that all narrative, in the most different forms of language produce a history, we find support in Paul Ricoeur's (1990) thought for which all history is narrative. In order to weave the narratives of individual memories that are confused with the collective memories and the own history of the black community we use Kabengele Munanga (1994) articulated to the thought wise and poetic of Hampaté Bâ (2003, 2010), author who discusses the relevance of the word for the inheritances of the African matrix. We also consider authors such as Clóvis Moura (1981) and Abdias de Nascimento (1980, 2003) to deal with issues of black territory, formation and formation of quilombo. Like Lélia Gonzalez (1982) and Eduardo de Oliveira (1977) among other fundamental authors in the reflection on the social, political, economic, cultural and intellectual organization of the Negro in Brazil. We conceptualize the communicative event of the narrative as a structured fabric that communicates, preserves and impresses meaning to a determined society, considering a specific historical and temporal context from Marcuschi's (2008) thought. We verified how this idea is effective in the narratives presented by the subjects surveyed in the Quilombo Serra do Apon Community. Within these narratives are present the oral aspects in the communicative stories and histories of life and the visual aspects, the photographs produced by the subjects participating in the research, treated as records of memories that flee from the words, shaping images that, in turn, demanded an adequacy within the research. The methodology, in which this work is constructed, allows us to interpret images, but we also support the critical interpretation that considers social roles and functions beyond the relations of power, by which these roles and functions can be linked, disregarding the sense of taste, of appreciation and pleasure. For this, visual culture was used in the perspective of Fernando Hernandez (2000). Our methodological course followed some participatory ethnographic techniques, not considering the ethnography in its totality and we use the Communicative - Critical Methodology (MCC) based on the thoughts of Jürgen Habermans (1987) on Communicative Action and on the concept of Dialogicity proposed by Paulo Freire (1994) , 2005), who assumed the role of method ora methodology in the structuring of all research. To understand all the aspects present in the work, we use authors such as Carmem Lúcia Guimarães de Mattos (2011), Clifford Geertz (1989), Fabiana Marine (2010), José Goméz (2006), Rafael Bisquerra (2004), Roseli Rodrigues de Mello 2010), Silionara Aparecida Madureira (2015), Vanessa Gabassa (2010) and others. The application of the techniques and methodology was favorable not only to reading and analyzing the content of the narratives - oral and visual - but also represented an understanding of the social, political, economic and cultural formation process of this community. We do not propose a rescue of the history and memory of these subjects, but rather the record of the possibilities of seeing, imagining, interpreting and re-signification the ways of narrating life presented by these subjects.